An ultra-fast, self-powered and flexible visible-light photodetector based on graphene/Cu2O/Cu gradient heterostructures. Issue 8 (2nd February 2021) - Cong, Lujia; Zhou, Haitao; Chen, Mingzhu; Wang, Hongbin; Chen, He; Ma, Jiangang; Yan, Siyi; Li, Bingsheng; Xu, Haiyang; Liu, Yichun
Abstract : Graphene/Cu2 O/Cu flexible self-powered photodetector has high visible light detection performance. This excellent performance is attributes to the inherent built-in electric field of the Cu2 O absorption layer. Abstract : Cuprous oxide (Cu2 O) is widely used in optoelectronic devices, because of its nontoxicity, high light absorption coefficient, native p-type conductivity and high hole mobility. Herein, a visible-light photodetector based on a graphene/Cu2 O/Cu device is synthesized by novel thermal oxidation of Cu foil with the assistance of carbon powder and mechanically transferring the monolayer graphene onto the surface of the Cu2 O. At zero bias voltage, the graphene/Cu2 O/Cu visible-light photodetector exhibits an ultra-fast response time of 4.1 μs at 530 nm, a responsivity of 86 mA W −1 at 550 nm and excellent visible-light selectivity. Besides, the graphene/Cu2 O/Cu device maintains high responsivity even after being bent thousands of times to a radius of curvature of 30 mm. Cross-sectional TEM and EDX measurements indicate that the ratio of copper to oxygen in the Cu2 O film increased gradually from the surface to the inside, which induces an inherent built-in electric field along the normal direction of the Cu2 O absorption layer and consequently a rapid separation of photo-generated carriers. Our research provides a new approach for developing self-powered flexible visible-light photodetectors with low cost, high efficiency and quick response.